IQAC – An Ace Strategy for Quality Sustenance and Enhancement in Higher Education - Dr. M. Venkataramana Reddy (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2011)
Quality is variously defined by various people from varied domains. If it is ‘zero defects’ for someone, it is ‘customer satisfaction’ and ‘customer delight’ for somebody. It is a moving target, it is the journey towards quality that makes one achieve Quality in the real sense of the term. NAAC, armed with the mandate provided by the UGC, set off in its efforts to assess and accredit institutions of higher learning in 1994. World over, accreditation bodies use Internal Quality assurance as a tool for quality sustenance and enhancement. NAAC, right from its inception has promoted the concept of IQAC in accredited Colleges as a post quality sustenance measure. IQAC is undoubtedly, a well thought over strategy to ensure that every HEI takes care of quality sustenance and enhancement